Enhancement of air stability and photovoltaic performance in organic solar cells by structural modulation of bis‐amide‐based donor‐acceptor copolymers: A computational insight. Issue 6 (28th October 2020) - Bhattacharya, Labanya; Sharma, Sagar; Sahu, Sridhar
Abstract: The effect of structural modulation on a series of donor‐acceptor (D‐A) copolymers (1 ‐7 ), comprising of thieno[3, 2‐ b ]thiophene (TT) donor and thiazole‐flanked different bis‐amide‐functionalized acceptor units, has been explored. Structural functionalization has been performed by incorporating aromatic rings in the bis‐amide‐functionalized bipyrrolylidene‐2, 2′(1 H, 1′ H )‐dione (BPD) (1 ) acceptor unit, and six D‐A copolymers containing isoindigo (2 ), azaisoindigo (3 ), benzoisoindigo (4 ), benzoazaisoindigo (5 ), 1, 5‐naphthyridine‐BPD (6 ), and 1, 8‐naphthyridine‐BPD (7 ) as acceptor units are designed. Density functional theory has been employed to understand the impact of structural modulation on geometrical, optoelectronic, charge transport, and photovoltaic properties of the copolymers. The higher proportion of N‐heteroatom in copolymers 3, 6, and 7 leads to low‐lying highest occupied molecular orbital (lowest unoccupied molecular orbital) levels and thus improves their air stability and open‐circuit voltage. The computed optical absorption in the visible range (602‐754 nm) ensures that the studied compounds can efficiently harvest photon energy. The ratio of charge transfer rate ( K CT ) and charge recombination rate ( K CR ) at donor/PC61 BM interfaces of structurally tuned copolymers are found to be ∼10 7 to 10 22 times higher than 1 /PC61 BM. The maximum predicted power conversion efficiency by Scharber diagram could reach up to ∼8% for 3, 6, and 7 . The calculated results shed light on the fact that the structural modulation of bis‐amide‐functionalized D‐A copolymers can efficaciously lead to enhanced air stability and photovoltaic performance. Abstract : The computational study shows that structural modulation of donor‐acceptor copolymer enhances the air‐stability and photovoltaic performance. The copolymers having higher proportion of N‐heteroatoms lead to deeper HOMO/LUMO levels and hence better air‐stability. Low‐lying HOMO increases the open circuit voltage for them. The interfacial charge transfer improves after structural tuning of the copolymers. The maximum predicted power conversion efficiency could reach up to ~8% for the copolymers using Scharber diagram.